The Influence of Profitability, Asset Structure, Firm Size, and Solvency on Capital Structure in Food and Beverage Companies - Velika Occalanie; Peter Peter; Henky Lisan Suwarno (International Journal of Economics, Commerce, and Management, 2026)
Food and beverage companies must maintain a robust capital structure to compete effectively amidst the intense pressures of globalization and achieve their strategic objectives. This study aims to examine the impact of profitability, asset structure, company size, and solvency on the capital structure of food and beverage firms listed on the Indonesia Stock Exchange (IDX) and included in the LQ45 index. This study uses an explanatory method with purposive sampling technique, where samples are determined based on companies that have completed financial reports during the research period and are indexed in LQ45. Data analysis was performed using t-tests and F-tests. The results show that profitability (ROA), asset structure, and company size (Ln Total Assets) do not have a significant partial effect on capital structure (DER), meaning that these three factors do not directly influence companies' decisions on the use of debt for financing. However, solvency (DAR) was found to have a significant effect on capital structure, indicating that a company's ability to meet its long-term obligations plays an important role in determining the level of debt used for operational financing. Simultaneously, the four independent variables had a significant effect on capital structure, meaning that all variables together contributed to influencing food and beverage companies' decisions in determining their financing strategies.